Secondary metabolites and bioactivity studies of Garcinia griffithii plant - Kamal, Tara; Omar, Muhammad Nor; Darnis, Deny Susanti; Taher, Muhammad (2010)
Nowadays, researchers are focusing their attention towards folk medicine for developing better drugs against microbial infections. Garcinia griffithii was assessed for active principles. The aim of this study is to isolate the active antimicrobial compounds from Garcinia griffithii plant. The plant materials were extracted using solvents with different polarities. The solvent extracts were then tested for antimicrobial activities based on bio-assay guided fractionation technique. It was found that the polar extracts, i.e. methanol and ethyl acetate, showed higher antimicrobial activities than the non polar (hexane) extract. The results of screening test for phytochmicals showed that the leave extract of the plant possessed the active principles e.g. terpenoids, tannins,alkaloids saponins and glycosides. The antimicrobial activity of the extracts was assayed against four bacteria and two fungal strains using the agar diffusion method by indicating the presence of the clear inhibition zones around each disc (Murray et al., 1999). Methanolic extract showed the highest inhibition zone of 18mm against S. aureus compared with Ethylacetast and Hexane extracts the bioactive compounds in methanol fraction was isolated by column chromatography on silica gel and eluted with chloroform: methanol (8.2). The minimum inhibitory concentration (MIC) and the minimum bacteria concentration (MBC) of the methanol isolated compound/s ranged from 0.013to 30mg/ml using 96 well diffusion methods. (Vollekova etal.2001 and Usman et al.,2007). MIC value for compound (1) 0.123mg/ml no MBC, MIC value for compound (2) 1.1mg/ml and MBC=MIC.